Diversity and ecological drivers of lichens on Kunashir Island (Kuril Islands, Russian Far East) - Anna S. Zueva; Sergey V. Chesnokov; Liudmila A. Konoreva; Ilya A. Prokopiev (Acta Biologica Sibirica, 2025)
The purpose of this study is to examine the diversity of lichens in different communities of Kunashir Island and to identify factors influencing their distribution on the island. In total, we identified 172 species of lichens and related fungi. Ochrolechia lijiangensis and Pertusaria plittiana are new to Russia. Amandinea pelidna, Bacidina brandii, and Lecanora caesiosora are new for the Russian Far East. Thirteen species are reported for the first time for the Sakhalin Region. Six species are new for the Kuril Islands and 37 are new for Kunashir Island. Most of the identified lichens are corticolous species. The richest in the number of lichen species are Abies sachalinensis, Betula ermanii, Quercus crispula, Picea ajanensis, Acer mayrii, Alnus hirsuta, and Salix udensis (25–40 species). It is shown that at the landscape level the only significant factor for the species composition of lichens is the community type, while at the substrate level, the coniferous or deciduous nature of the substrate and the acidity of the bark have an impact.